2017
DOI: 10.1200/jco.2017.74.7642
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-Ligand 1 Immunohistochemistry Testing: A Review of Analytical Assays and Clinical Implementation in Non–Small-Cell Lung Cancer

Abstract: Purpose Three programmed death-1/programmed death-ligand 1 (PD-L1) inhibitors are currently approved for treatment of non-small-cell lung cancer (NSCLC). Treatment with pembrolizumab in NSCLC requires PD-L1 immunohistochemistry (IHC) testing. Nivolumab and atezolizumab are approved without PD-L1 testing, though US Food and Drug Administration-cleared complementary PD-L1 tests are available for both. PD-L1 IHC assays used to assess PD-L1 expression in patients treated with programmed death-1/PD-L1 inhibitors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
288
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(306 citation statements)
references
References 35 publications
15
288
1
2
Order By: Relevance
“…Irrespective of the assay used, atezolizumab was shown to improve survival in patients with PD-L1-negative tumors, confirming the original findings of the trial [15]. Other studies have demonstrated high concordance between most PD-L1 IHC assays, but have not correlated these data with clinical results [16][17][18]. Efforts are underway by the pharmaceutical industry and regulators to harmonize these diagnostic tests.…”
mentioning
confidence: 73%
“…Irrespective of the assay used, atezolizumab was shown to improve survival in patients with PD-L1-negative tumors, confirming the original findings of the trial [15]. Other studies have demonstrated high concordance between most PD-L1 IHC assays, but have not correlated these data with clinical results [16][17][18]. Efforts are underway by the pharmaceutical industry and regulators to harmonize these diagnostic tests.…”
mentioning
confidence: 73%
“…KEYNOTE‐028 only included patients who were screened as positive for the PD‐L1 biomarker (also defined as >1% PD‐L1 expression in both tumour and immune cells). Second, the two trials analysed PD‐L1 as a binary rather than continuous variable, despite the impact of the latter on clinical outcomes . Whether the benefit of nivolumab or pembrolizumab dissipated with lower levels of PD‐L1 expression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed death ligand 1 (PD‐L1) is a transmembrane protein expressed on immune cells (IC) and tumour cells (TC), whereas programmed cell death (PD)‐1 is expressed on IC and its expression can be induced following T cell activation. Upon binding to the receptor PD‐1 in IC, the overexpressed PD‐L1 in TC leads to functional inactivation of T cells and down‐regulation of T cell antitumoral activity, resulting in immune evasion . In recent years, PD‐L1 and PD‐1 have emerged as a key check‐point that can be manipulated with inhibitory monoclonal antibodies in various cancer types.…”
Section: Introductionmentioning
confidence: 99%